Management of isoniazid-monoresistant tuberculosis (Hr-TB) in Queensland, Australia: a retrospective case series. (November 2020) - Wilson, Malcolm; O'Connor, Bridget; Matigian, Nicholas; Eather, Geoffrey
Abstract: Objectives: Drug-resistance represents a major threat in the fight against tuberculosis. Globally, isoniazid-monoresistant tuberculosis (Hr-TB) is twice as common as multidrug/rifampicin-resistant (MDR/RR)-TB. Recently updated WHO guidelines now recommend treatment of Hr-TB with rifampicin, ethambutol, pyrazinamide and levofloxacin for at least six months. Our primary objective was to define the frequency, treatment and outcomes for Hr-TB in Queensland, Australia. We also sought to determine the frequency of fluoroquinolone use and whether its inclusion improved outcomes. Methods: Retrospective case series of tuberculosis notifications in Queensland between 2000 and 2017 with at least low-level isoniazid resistance and preserved susceptibility to other first-line oral agents. Results: Hr-TB was identified in 7.2% of all notifications. Where outcomes were assessable (163/198), 76.1% were treated with first-line agents only and 11.0% received at least six months of a fluoroquinolone-containing regimen (consistent with recent WHO guidelines). Favourable outcomes were achieved in 95.7%, comparable to fully susceptible disease (94.9%). Inclusion of a fluoroquinolone did not significantly improve outcomes compared with a regimen containing first-line agents only, although these cases were more likely to have high-level resistance. Previous treatment made an unfavourable outcome more likely. Conclusions: Hr-TB is prevalent in Queensland. Treatment outcomes in our cohort were comparable to fully susceptible disease. The current WHO-recommended regimen did not confer advantage over an appropriately constructed regimen containing first-line agents only. Our findings suggest that, in a well-resourced setting with good programmatic management, the addition of a fluoroquinolone may not substantially improve outcomes – potentially allowing these agents to be reserved for more extensively resistant disease. Highlights: 198 cases of Hr-TB were identified in Queensland, Australia between 2000 and 2017. The prevalence of 7.2% is comparable to the global rate amongst new cases. Favourable outcomes were achieved in 95.7% of cases. This was comparable with outcomes for fully susceptible disease (94.9%). And not improved by including a fluoroquinolone as recommended by WHO guidelines.